The Antitoxin Protein of a Toxin-Antitoxin System from Xylella fastidiosa Is Secreted via Outer Membrane Vesicles - Santiago, André da Silva; Mendes, Juliano S.; Santos, Clelton A. dos; Toledo, Marcelo A. S. de; Beloti, Lilian L.; Crucello, Aline; Horta, Maria A. C.; Favaro, Marianna T. de Pinho; Munar, Duber M. M.; Souza, Alessandra A. de; Cotta, Mônica A.; Souza, Anete P. de (Frontiers in Microbiology, 2016)
The Xylella fastidiosa subsp pauca strain 9a5c is a Gram-negative, xylem-limited bacterium that is able to form a biofilm and affects citrus crops in Brazil. Some genes are considered to be involved in biofilm formation, but the specific mechanisms involved in this process remain unknown. This limited understanding of how some bacteria form biofilms is a major barrier to our comprehension of the progression of diseases caused by biofilm-producing bacteria. Several investigations have shown that the toxin-antitoxin (TA) operon is related to biofilm formation. This operon is composed of a toxin with RNAse activity and its cognate antitoxin. Previous reports have indicated that the antitoxin is able to inhibit toxin activity and modulate the expression of the operon as well as other target genes involved in oxidative stress and mobility. In this study, we characterize a toxin-antitoxin system consisting of XfMqsR and XfYgiT, respectively, from X. fastidiosa subsp pauca strain 9a5c. These proteins display a high similarity to their homologues in X. fastidiosa strain Temecula and a predicted tridimensional structure that is similar to MqsR-YgiT from Escherichia coli. The characterization was performed using in vitro assays such as analytical ultracentrifugation (AUC), size exclusion chromatography, isothermal titration calorimetry and western blotting. Using a fluorometric assay to detect RNAses, we demonstrated that XfMqsR is thermostable and can degrade RNA. XfMqsR is inhibited by XfYgiT, which interacts with its own promoter. XfYgiT is known to be localized in the intracellular compartment; however, we provide strong evidence that X. fastidiosa secretes wild-type XfYgiT into the extracellular environment via outer membrane vesicles, as confirmed by western blotting and specific immunofluorescence labeling visualized by fluorescence microscopy. Taken together, our results characterize the TA system from X. fastidiosa strain 9a5c, and we also discuss the possible influence of wild-type XfYgiT in the cell.